The Role of Image Generative Artificial Intelligence in Optimizing Digital Visual Assets for Animation and Motion Graphics Content - B Azhar, Iman Saladin; Sari, Winda Kurnia; Exaudi, Kemahyanto; Prasetyo, Aditya Putra Perdana (Institut Teknologi Nasional, Bandung, 2025)
This Community Service Program (PKM) was conducted to introduce and promote the use of Motion Graphics and Image Generative AI technologies as innovative tools to support digital content creation, particularly in the context of industry and government institutions. Through a workshop format, participants were provided with an overview of how these technologies can improve the quality, clarity, and appeal of visual communication. The session included a conceptual explanation of Image Generative AI, such as Adobe Firefly, which allows users to generate visual assets through text prompts, and Adobe After Effects, a powerful tool for producing dynamic animations and motion graphics. Participants actively followed the material presented and showed interest in how these tools can be applied in real-world promotional or branding efforts. The workshop concluded that integrating these technologies holds great potential for enhancing institutional communication strategies. Future programs are expected to include more hands-on and practice-oriented sessions to further develop participants’ digital production skills.